Ethics, medical ethics, and occupational medicine: is their dialogue possible? - Buzzi, Elisa (La Medicina del Lavoro, 2016)
Today’s medicine faces some critical moral challenges, yet the medical class suffers from an increasingly evident malaise: a growing dissatisfaction with an ethical demand often perceived as a cumbersome burden of rules and prohibitions, which risk to erode the fiduciary relations with patients. Such a negative appraisal is partly due to a narrow interpretation of the meaning of ethics, a misconception whose roots are in the positivistic stance that permeates our culture, and in its almost exclusively technological bent. This radical orientation of our culture shows itself in the vanishing of the idea of an intrinsic ethical dimension of medicine and consequent eclipse of traditional medical ethics, currently all but assimilated by bioethics. Maintaining a clear distinction between medical ethics and bioethics is a fundamental condition for guaranteeing an original ethical reflection in medicine, thereby fostering a constructive dialogue between philosophical and medical ethics. In this sense, occupational medicine holds a very propitious position, at the cross-roads to some of the most important dimensions in human life and society: health, work, environment. In a milieu which is too often inclined to efface the living human being and the deepest needs of humanity, the moral commitment of medical profession to the care of the integral reality of the embodied human person is one of the most important ethical challenges facing occupational medicine and a most valuable contribution to the current ethical debate.